2019
DOI: 10.1186/s13578-019-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

Communication between mitochondria and other organelles: a brand-new perspective on mitochondria in cancer

Abstract: Mitochondria are energy factories of cells and are important pivots for intracellular interactions with other organelles. They interact with the endoplasmic reticulum, peroxisomes, and nucleus through signal transduction, vesicle transport, and membrane contact sites to regulate energy metabolism, biosynthesis, immune response, and cell turnover. However, when the communication between organelles fails and the mitochondria are dysfunctional, it may induce tumorigenesis. In this review, we elaborate on how mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
145
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 149 publications
1
145
0
Order By: Relevance
“…LncRNA can regulate the transcription and post‐transcriptional activity of target genes to exert distinctive biological functions in the pathogenesis of cancer. In fact, certain lncRNA can directly bind to target proteins and regulate their localization (Duan et al ., 2019; Xia et al ., 2019), stabilization, and post‐translational modifications (Fan et al ., 2017). Hence, lncRNA employ various molecular interaction models to influence the initiation, progression, and metastasis of cancer (Deng et al ., 2018; Fan et al ., 2019c).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA can regulate the transcription and post‐transcriptional activity of target genes to exert distinctive biological functions in the pathogenesis of cancer. In fact, certain lncRNA can directly bind to target proteins and regulate their localization (Duan et al ., 2019; Xia et al ., 2019), stabilization, and post‐translational modifications (Fan et al ., 2017). Hence, lncRNA employ various molecular interaction models to influence the initiation, progression, and metastasis of cancer (Deng et al ., 2018; Fan et al ., 2019c).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant cell proliferation is one of the hallmarks of tumor cells [82][83][84][85][86]. Research has shown that c-Myc can promote the transcription of positive cell cycle regulatory factors, such as E2F transcription factors, cyclin D1, and cyclin-dependent kinase 4 (CDK4).…”
Section: Pvt1 Participates In the Proliferation-related Signaling Patmentioning
confidence: 99%
“…In recent years, a large body of literature has shown that the BRAF V600E mutation is associated with a series of adverse clinical pathological factors in PTC, such as advanced disease, invasive characteristics, and others [8][9][10][11][12][13][14]. Many studies have shown that the BRAF V600E mutation may result in the activation of downstream genes of the MAPK pathway, which may lead to a slight downregulation of the sodium iodide symporter (NIS), thereby causing an inaccurate NIS localization wherein the NIS cannot be accurately localized to the cell membrane [15,16]. This failure of proper localization leads to a decrease in the ability of tumor cells to take up iodine [17,18].…”
Section: Introductionmentioning
confidence: 99%